Interaction between zoonotic bacteria and free living amoebas. A new angle of an epidemiological polyhedron of public health importance? - Simaluiza Masabanda, R. (2015)
Since many years ago, several studies reported the endosimbisis between bacteria species and free living amoebas. However, the mechanisms involved in the bacteria penetration and release from the amoeba are not clear. The free living amoebas especially Acanthamoeba castellanii are considered important bacteria predators, for that reason they have a significant role in the control of microbial populations in particular environments. However, some bacteria are capable to avoid the digestion from the amoeba and take advantage of this intimate relationship. A. castellanii is a ubiquitous organism present in aquatic and soil environments. Particularly in humid environments that they could share with different bacteria species, including those pathogen for humans transmitted by animals. The interaction between the bacteria and the amoebas may result in a close endosimbiotic relationship that allows the bacteria to survive inside the vacuoles of the protozoa for days or months. The purpose of this review is to describe the relevant aspects of the interaction between A. castellanii and different bacteria species, mostly those with relevance in public health and related with zoonosis.